Histórico de uso e estrutura da vegetação arbórea das Ilhas Florestais em Alter do Chão – Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this work was to evaluate and to relate the effect of anthropic action on the tree structure of the forest islands (FI) of the Environmental Protection Area (EPA) of Alter do Chão, located in Santarém, Pará, Brazil. An anthropogenic disturbance indicator with semi-structured interviews was constructed to classify the FIs for the degree of anthropic disturbance and to compare the least disturbed and most disturbed FIs by pairs, controlling the size and distance of the continuous forest. We interviewed 15 people who lived in the region for more than 30 years. The interviews also revealed the main useful forest species and their uses. Trees were measured within plots with an area of 10x250 m. The trees measured in the first two meters of width from the center line had diameter at chest height DCH≥1 cm, in the remaining eight meters trees were. measured with DCH≥10 cm. The value of use (VU) of useful forest species was determined by dividing the number of uses of the species by the number of respondents. A total of 2,334 trees with an average of 172 individuals (± 52.08) for most disturbed FIs and 215 (± 87.71) for less disturbed FIs were measured; mean baseline area 32899.89 cm² (± 13497.89) in the most disturbed FIs and 44391.83 cm² (± 10882.29) in the least disturbed FIs. The most useful forest species according to the interviewees were Camaen (Casearia commersoniana Cambess), with VU = 6 and Carapucuzeiro (Myrcia hatschbachii D. Legrand), with VU = 5.8, as woody uses. The most important non-timber species were Carapanaúba (Aspidosperma macrocarpon Mart.), With VU = 3 and Envira Branca (Cochlospermum orinocense (Kunth) Steud), with VU = 2. Useful species are more present in less disturbed and larger IFs. In three pairs of FI the mean cross-sectional area (CSA) was higher in those less disturbed. In the more disturbed FIs there are less useful forest species and have a lower total basal area, but statistical tests made to compare their tree structures were not significant.
Keywords: Unidade de Conservação; Etnoespécies; Fogo; Produtos Florestais; Madeiráveis; CNPQ::CIÊNCIAS BIOLÓGICAS; ESTUDOS E MANEJOS DOS ECOSSISTEMAS AMAZÔNICOS